Changes in lipids and aroma compounds in intramuscular fat from Hu sheep. (30th July 2022) - Li, Jing; Yang, Youyou; Tang, Chaohua; Yue, Shengnan; Zhao, Qingyu; Li, Fadi; Zhang, Junmin
Highlights: Intramuscular fat (IMF) content varied between individual Hu sheep. Increasing triglycerides and diglycerides led to an increase in IMF content. Lipid-derived compounds mainly contributed to the differences in aroma. Differences in aroma may be related to thermal oxidation of unsaturated fatty acids. Abstract: Intramuscular fat (IMF) content is associated with lamb flavor and largely varies between individuals of the same breed. However, studies investigating the effects of IMF variations on lipid profiles and aroma compounds are limited. Here, we performed lipidomic and volatilomic profiling of high-IMF and low-IMF Hu lambs. Triglycerides and diglycerides in the high-IMF group were significantly higher than those in the low-IMF group ( p < 0.05). Seventy-nine of 842 lipids identified were significantly different between the groups under positive and negative ion modes (variable importance in projection > 1, p < 0.05). Volatilomic analyses revealed that the aroma profiles also differed between the groups. Fifteen aroma compounds, mainly originating from lipid oxidation, could be responsible for this difference. Thus, our findings provide a comprehensive understanding of the increases in IMF content that drive consumers' satisfaction and also provide a basis for underpinning breeding value for IMF.